Echocardiographic Evaluation in Neonates with Heart Murmurs - Ahmadipour, Shokoufeh; Mohsenzadeh, Azam; Soleimaninejad, Maryam (Journal of Pediatric Intensive Care, 2018)
Auscultation of the heart is one of the most important tools of physical examination in neonates, which is very helpful in the diagnosis or rejection of congenital heart diseases (CHDs). The aim of this study is to investigate the causes of heart murmur in neonates hospitalized in neonatal unit in Imam Reza Hospital, Kermanshah, Iran. This cross-sectional study was conducted within the period of 18 months on neonates hospitalized in neonatal unit whose heart murmur, diagnosed through examination, and echocardiography was conducted to investigate the existence of CHD. In 62.1% of the cases, murmuring was auscultated within the first week after birth. Among 172 neonates with heart murmur, 25 subjects (14.5%) had normal echocardiogram, and others had abnormal echocardiogram in which ventricular septal defect (31.4%) was the most common CHD. Patent ductus arteriosus (23.3%) was the second common CHD found. Other defects were atrial septal defect, persistent foramen ovale, pulmonary stenosis, and tricuspid regurgitation. Among the neonates with CHD, 55 subjects were females and 92 cases were males. There was CHD history in previous siblings in 10 cases. In 73 neonates with CHD, the mother had not taken folic acid in the first trimester of pregnancy. A total of 14.5% of the hospitalized neonates suffered from innocent murmur, and the rest with heart murmur had abnormal echocardiography and suffered from CHD (85.5%). Heart murmur in neonates could be a symptom of CHD, and timely echocardiography is very important in diagnosing the type of disease.
Keywords: neonates; murmur; echocardiography